Answer:
V=11
Step-by-step explanation:
Simplify:
14V-5V+5=4V+60
9V+5=4V+60
Subtract 4V on both sides:
9V-4V+5=4V-4V+60
Solve:
5V+5=60
Subtract 5 on both sides:
5V+5-5=60-5
5V=55
Divide by 5
V=11
Hope this helps!
Step-by-step explanation:
14V+ 5 - 5V= 4V+ 60|-60|-4V
14V + 5 -5 V - 60 - 4V =0
<=> 5V - 55 =0 |+55
<=> 5V = 55 |:5
<=> V= 11
(2) 3x⁴-4x³+7x-2 from 9-7x⁴+6x³-2x²-11x
Answer:
1) 5y + 5z
2) 10x⁴ - 10x³ + 2x² + 18x - 11
Step-by-step explanation:
Given the subtraction of the following polynomial expressions:
In order to make it easier for us to perform the required mathematical operations, we must first rearrange the terms in the subtrahend by alphabetical order.
-3x - 4y + 11z
-3x - 9y + 6z ⇒ This is the subtrahend.
Now, we can finally perform the subtraction on both trinomials:
In the subtrahend, the coefficients of x and y are both negative. Thus, performing the subtraction operations on these coefficients transforms their sign into positive.
The difference is: 5y + 5z.
Similar to the how we arranged the given trinomials in Question 1, we must rearrange the given polynomials in descending degree of terms before subtracting like terms.
3x⁴- 4x³ + 7x - 2 ⇒ Already in descending order (degree).
9 - 7x⁴ + 6x³- 2x² - 11x ⇒ -7x⁴ + 6x³- 2x² - 11x + 9
In subtracting polynomials, we can only subtract like terms, which are terms that have the same variables and exponents.
In the minuend, I added the "0x²" to make it less-confusing for us to perform the subtraction operations.
The same rules apply in terms of coefficients with negative signs in the subtrahend, such as: -7x⁴, - 2x², and - 11x ⇒ their coefficients turn into positive when performing subtraction.
Therefore, the difference is: 10x⁴ - 10x³ + 2x² + 18x - 11.
-3
15
3
Please help.
Answer:
D. 3
Step-by-step explanation:
Assuming the model represents an equation, the following can be deduced:
On the left side of the equation, the model shows we have 3 "x's", and 6 "1's". Let this represent:
3x + 6
On the right side of the equation, we have 2 "x's" and 9 "1's". Let this represent:
2x + 9.
The model would represent the equation below:
Solve for x
(Subtracting 2x from both sides of the equation)
(subtracting 6 from both sides of the equation)
Answer:
52
Step-by-step explanation:
78 divided by 3 is 26
26 times 2 is 52